Mutations in SIX1 Associated with Branchio-oto-Renal Syndrome (BOR) Differentially Affect Otic Expression of Putative Target Genes - Tanya Mehdizadeh; Himani D. Majumdar; Sarah Ahsan; Andre L. P. Tavares; Sally A. Moody (Journal of Developmental Biology, 2021)
Several single-nucleotide mutations in SIX1 underlie branchio-otic/branchio-oto-renal (BOR) syndrome, but the clinical literature has not been able to correlate different variants with specific phenotypes. We previously assessed whether variants in either the cofactor binding domain (V17E, R110W) or the DNA binding domain (W122R, Y129C) might differentially affect early embryonic gene expression, and found that each variant had a different combination of effects on neural crest and placode gene expression. Since the otic vesicle gives rise to the inner ear, which is consistently affected in BOR, herein we focused on whether the variants differentially affected the otic expression of genes previously found to be likely Six1 targets. We found that V17E, which does not bind Eya cofactors, was as effective as wild-type Six1 in reducing most otic target genes, whereas R110W, W122R and Y129C, which bind Eya, were significantly less effective. Notably, V17E reduced the otic expression of prdm1, whereas R110W, W122R and Y129C expanded it. Since each mutant has defective transcriptional activity but differs in their ability to interact with Eya cofactors, we propose that altered cofactor interactions at the mutated sites differentially interfere with their ability to drive otic gene expression, and these differences may contribute to patient phenotype variability.